International listed real estate returns: evidence from the global financial crisis. Issue 1 (4th February 2019) - Coën, Alain; Lecomte, Patrick
Abstract : Purpose: The purpose of this paper is to analyze and revisit the risk and performance of publicly traded real estate companies from 14 countries over the period 2000–2015, marked by the unprecedented Global Financial Crisis, in presence of errors-in-variables (EIV) and illiquidity (measured by serial correlation, following Getmansky et al. (2004)). Design/methodology/approach: The authors extend the seminal work of Bond et al. (2003), and shed a new light on the relative performance of listed real estate before and after the GFC. First, the authors suggest the use of various asset pricing models (APM) including the Fama and French (2015) five-factor APM with global and country-level factors. Second, the authors implement unbiased estimators to correct for the econometric bias induced by EIV in APM. Third, the authors deal with the impact of illiquidity (measured by serial correlation) on the risk properties of international securitized real estate returns. Findings: The findings show that post-GFC, a radical change in international listed real estate risk factors has resulted in more homogeneous markets internationally and less diversification opportunities for international investors. Practical implications: The authors suggest the use of robust linear APM (including the Fama and French (2015) five-factor APM) to analyze the risk and performance of publicly traded real estate companies from 14 countries over the period 2000–2015. Originality/value: The authors analyze and revisit the risk and performance of publicly traded real estate companies from 14 countries over the period 2000–2015, marked by the unprecedented Global Financial Crisis.